EVALUASI USABILITY SISENSI MOBILE MENGGUNAKAN METODE ISO/IEC 9126 DAN NIELSEN MODEL - Ayu Lestari; Wafiah Murniati; Saikin; Hasyim Asyari (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
The Mobile Attendance and Presence Information System (SISENSI) is an online attendance application that has problems or shortcomings, such as requiring a long time to be absent and lacking a leave permit feature so that users have difficulty applying for leave permission. Therefore, the aim of this research is to test the SISENSI mobile application to determine the quality and shortcomings of the application. The usability evaluation methods that will be used are ISO/IEC 9126 and Nielsen Model. The results of combining ISO/IEC 9126 and the Nielsen Model obtained eight SISENSI Mobile testing factors in the usability field, namely understandability, learnability, operability, attractiveness, memorability, efficiency, errors, and user satisfactions. Respondents in this study were 164 people. The results of this research obtained values for each sub-characteristic namely: understandability 84%, learnability 80%, operability 80%, attractiveness 69%, efficiency 82%, memorability 67%, errors 75% and user satisfactions 65%. Meanwhile, the average value is 75%, so overall SISENSI Mobile is in good condition.